영구치 치수 기질세포를 이용한 연골 분화 및 분화 시기에 따른 형태학적 변화 - 정주령; 김하나; 박열; 김민정; 오영주; 신수정; 최윤정; 김경호; Chung, Choo-Ryung; Kim, Ha-Na; Park, Yeul; Kim, Min-Jeong; et al. (Restorative dentistry & endodontics, 2012)
Objectives: The aim was to confirm the stem cell-like properties of the dental pulp stromal cells and to evaluate the morphologic changes during in vitro chondrogenesis. Materials and Methods: Stromal cells were outgrown from the dental pulp tissue of the premolars. Surface markers were investigated and cell proliferation rate was compared to other mesenchymal stem cells. Multipotency of the pulp cells was confirmed by inducing osteogenesis, adipogenesis and chondrogenesis. The morphologic changes in the chondrogenic pellet during the 21 day of induction were evaluated under light microscope and transmission electron microscope. TUNEL assay was used to evaluate apoptosis within the chondrogenic pellets. Results: Pulp cells were CD90, 105 positive and CD31, 34 negative. They showed similar proliferation rate to other stem cells. Pulp cells differentiated to osteogenic, adipogenic and chondrogenic tissues. During chondrogenesis, 3-dimensional pellet was created with multi-layers, hypertrophic chondrocyte-like cells and cartilage-like extracellular matrix. However, cell morphology became irregular and apoptotic cells were increased after 7 day of chondrogenic induction. Conclusions: Pulp cells indicated mesenchymal stem cell-like characteristics. During the in vitro chondrogenesis, cellular activity was superior during the earlier phase (within 7 day) of differentiation.